2021
DOI: 10.3390/medicina57101129
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Healing of Non-Infected Stagnated Diabetic Wounds by Copper Oxide-Impregnated Wound Dressings

Abstract: Background and Objective: Copper, a wide spectrum biocide, also plays a key role in angiogenesis and wound healing. Antibacterial wound dressings impregnated with copper oxide microparticles (COD) have been recently cleared by the U.S. FDA and other regulatory bodies for the treatment of acute and chronic wounds, including diabetic wounds. Our objective was to evaluate the capacity of COD in stimulating the healing of non-infected stagnated wounds in diabetic patients initially treated with standard of care (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…Meaningfully, the capacity of copper dressings to stimulate wound healing of noninfected stagnated wounds in diabetic patients was also demonstrated. 22 Several clinical case reports that T A B L E 2 Inclusion/exclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meaningfully, the capacity of copper dressings to stimulate wound healing of noninfected stagnated wounds in diabetic patients was also demonstrated. 22 Several clinical case reports that T A B L E 2 Inclusion/exclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
“…This was further substantiated by Das et al, 30 who demonstrated in wild mice that exogenous and endogenous Cu promote wound healing through the endothelial antioxidant‐1 (Atox 1) cytosolic Cu chaperone. Meaningfully, the capacity of copper dressings to stimulate wound healing of noninfected stagnated wounds in diabetic patients was also demonstrated 22 . Several clinical case reports that demonstrated enhanced wound healing of hard‐to‐heal wounds by copper dressings in patients suffering from other etiologies were also reported 20,21,31 .…”
Section: Discussionmentioning
confidence: 98%
“…Wound dressings impregnated with cuprous oxide microparticles have been cleared by the USA FDA (510(k) K180643), EU and other regulatory bodies worldwide to be used in the management of acute and chronic wounds, after their biocompatibility, safety, and efficacy were demonstrated. These wound dressings have already been in clinical use for more than 2 years in several geographies, enhancing wound healing of both infected and non-infected wounds, including chronic wounds [15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…The development, safety, and biocidal properties of prototype antimicrobial wound dressings containing copper oxide microparticles were previously described [14]. In the current article, we describe the in vitro biocidal activity of significantly improved wound dressings impregnated with cuprous oxide microparticles that have been cleared for use by several regulatory bodies and started recently to be in use for the management of acute and chronic wounds [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Another approach to designing advanced textile dressings involves the addition of micro and nanoparticles. As an example, Melamed et al [ 106 ] have investigated copper oxide microparticle (COD)-impregnated wound dressings for the treatment of wounds in diabetic patients. The authors reported that COD significantly influenced the healing of hard-to-deal diabetic wounds, providing antibacterial effects, and directly enhancing the process.…”
Section: Wound Dressingsmentioning
confidence: 99%